Designing an Excellence-Oriented Foresight Model of Positive Psychology Dimensions for Enhancing Students’ Academic Progress and Academic Buoyancy - Ahmadi, Talat; Yarahmadi, Yahya (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to design a future-oriented excellence model based on positive psychology dimensions to explain and enhance students’ academic buoyancy and academic progress toward the 1414 national educational horizon. Methods and Materials: This study employed an applied mixed-methods exploratory sequential design grounded in a futures studies approach. The research population consisted of educational experts, policymakers, academic staff, educational psychologists, school administrators, and foresight specialists in Kurdistan Province. Purposeful sampling was conducted in two stages. First, semi-structured interviews were carried out with 23 experts until theoretical saturation was achieved. Subsequently, a 10-member strategic panel was formed to conduct structural analysis. Data collection instruments included a semi-structured interview protocol and a structured MICMAC questionnaire. Qualitative data were analyzed using systematic thematic analysis, resulting in the extraction of base, organizing, and overarching themes. Structural interactions among identified variables were examined using MICMAC software to calculate influence–dependence relationships, matrix stability, and system dynamics. Scenario development was conducted using a 2×2 scenario matrix combined with conceptual synthesis to construct the final excellence-oriented model. Findings: Structural analysis of the 11×11 interaction matrix indicated a system characterized by high interdependency and dynamic instability, reflecting complex interactions among psychological, pedagogical, technological, and governance factors. The matrix demonstrated 33.79% density with optimized stability after two rotations, confirming the robustness of expert judgments. Key driving variables included motivational–supportive learning ecosystems, transformative learning-centered assessment, and active deep pedagogy, which exerted strong direct influence on learner agency and technology-enhanced learning. Bidirectional variables such as teacher professional transformation, smart technology integration, and future-oriented educational governance showed both high influence and dependency. Dependent variables included innovative educational ecosystems, holistic learning systems, flexible differentiated learning, and self-directed learner development. Results indicated that systemic improvement in assessment practices and supportive learning environments functions as the principal leverage mechanism for strengthening academic buoyancy and long-term academic progress. Conclusion: The findings demonstrate that academic buoyancy cannot be improved through isolated psychological interventions but requires an integrated excellence framework combining positive psychology capacities, adaptive pedagogy, technological learning environments, collaborative educational networks, and future-oriented governance. The proposed foresight-based model provides a systemic roadmap for educational transformation by aligning individual psychological strengths with institutional innovation and policy development, thereby enabling sustainable enhancement of students’ academic vitality and achievement in future educational systems.